THE CONUNDRUM OF INTESTATE SUCCESSION FOR MUSLIMS IN UGANDA: Qadhis Court, Women’s Rights, and Islamic Inheritance Law Issues - Mujuzi, Jamil Ddamulira (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2023)
During the 2018–2022 process to amend the Succession Act, Muslims in Uganda requested a separate law to regulate their inheritance. However, this was rejected by the Parliamentary Committee. As a result, Muslims are governed by the Succession Act for intestate succession. This article aims to examine the legal uncertainty regarding the status of Qadhis' courts in Uganda and its impact on the unclear enforcement of Muslim inheritance law, particularly intestate succession, through these courts. Relying on the case law study, it is safe to argue that Qadhis’ courts do not exist legally. Although the Constitution provides for the right to equality, allowing Muslims to follow Sharia in the distribution of an estate can be justified under the Constitution's guarantee of equality, as long as the rights of individual Muslims are balanced against the interests of the Muslim community. Overall, navigating the legal landscape of inheritance for Muslims in Uganda is a complex issue with various legal and practical considerations.[Selama proses amandemen Undang-Undang Kewarisan pada 2018–2022, umat Islam di Uganda meminta undang-undang terpisah untuk mengatur kewarisan mereka. Namun, hal itu ditolak oleh Komite Parlemen. Akibatnya, umat Islam diatur oleh Undang-Undang Kewarisan yang lama. Artikel ini bertujuan untuk mengkaji ketidakpastian hukum mengenai status pengadilan Qadhis di Uganda dan dampaknya terhadap penegakan hukum kewarisan Muslim, khususnya kewarisan tanpa wasiat. Berdasarkan studi kasus, dapat dikatakan bahwa pengadilan Qadhis tidak ada secara legal. Meskipun Konstitusi memberikan hak atas kesetaraan, mengizinkan umat Islam untuk mengikuti Syariah dalam pembagian harta waris dapat dibenarkan di bawah jaminan konstitusi atas kesetaraan, selama hak-hak individu Muslim seimbang dengan kepentingan komunitas Muslim. Secara keseluruhan, menavigasi lanskap hukum kewarisan bagi umat Islam di Uganda merupakan masalah yang kompleks dengan berbagai pertimbangan hukum dan praktis.]